Synthesis of heterogeneous catalyst for biodiesel production - Tan, Hong Shen (2024)
Biodiesel is an intriguing replacement of petroleum diesel, which plays a direct role in advancing Sustainable Development Goal (SDG) 7 (“Affordable and Clean Energy”) and SDG 13 (“Climate Action”). However, the current production of biodiesel through the conventional transesterification process is plagued by inefficiency and waste by-product generation. Interesterification poses as a potential alternative to produce biodiesel with more upsides. However, the research of catalyst for interesterification is still lacking, particularly in heterogeneous catalysts. By using two types of biomass, microcrystalline cellulose and corncob, a functional sulfonated carbon-based catalyst was obtained. The catalyst was synthesised through a conventional two-step method consisting of a 2 hours carbonisation step and a 4 hours sulfonation step, where it was determined that the optimal carbonisation temperature is 200 °C and the optimal sulfonation temperature is 100 °C. The synthesised catalysts shown amorphous crystal structure and have no apparent porosity, with the highest observed specific surface area being 1.93 m2/g. However, the attachment of the functional group, sulfonic group, onto the catalyst surface is successful and comparable with other studies, where the highest sulfonic group density of 1.04 mmol/g was achieved. For the interesterification, methyl acetate and oleic acid was mixed at a molar ratio of 50:1 and reacted at a reaction temperature of 100 °C. As a result, the synthesised catalyst managed to achieve a reasonable optimal biodiesel yield of 82 % at a catalyst loading of 10 wt% and a reaction time of 4 h. While the synthesised catalyst have good thermal stability at the reaction temperature of 100 °C employed in this report, it suffered a noticeable decrease in activity due to leaching as the spent catalyst can only achieve a maximum biodiesel yield of 65 %, signalling that further study is required to improve the stability of the catalyst against leaching. This study provides more insight into the potential of sulfonated carbon-based catalysts from biomass to catalyse the production of biodiesel, which could ultimately help advance the progress of the UN SDGs, in particular SDG 7 and SDG 13.